Hubungan Beban Kerja Fisik dan Kelelahan Kerja Dengan Unsafe Actions Pada Pekerja Bagian Tanning UPT Industri Kulit Magetan - Mey Puspita Sari; Bachtiar Chahyadhi; Yeremia Rante Ada (Sekolah Vokasi, Universitas Sebelas Maret, 2022)
The rapid development of industrialization has resulted in the emergence of problems in the world of work, namely the emergence of work accidents. Work accidents can occur due to unsafe actions and unsafe condition. Physical workload affects the physiological condition of workers, workers who receive physical workloads that exceed capacity can cause fatigue which results in feelings of boredom and decreased concentration and alertness of workers, so that from these conditions will cause workers to experience negligence or unsafe actions while working,The sampling technique in this study used a total sampling technique with a total of 70 respondents. To measure the physical workload using a pulseoximeter, measuring work fatigue with the KAUPK2 questionnaire, and measuring unsafe actions with a questionnaire. The bivariate analysis technique used is the Somers'd test and the multivariate analysis used is the ordinal logistic regression test. The statistical test results show that the physical workload variable has a p-value = 0.000 (<0.05) and the work fatigue variable has a p-value = 0.000 (<0.05). Based on the results of the ordinal logistic regression test, it is known that the variable most related to unsafe actions is work fatigue with a wald value of 16,014.